Nigella sativa Averts 5-Fluorouracil Induced Kidney Injury via Targeting Redox Imbalance and MAPK Pathway - Alharthy, Khalid M; Rashid, Summya (Indian Journal of Pharmaceutical Education and Research, 2024)
Introduction: Chemotherapy-induced organ toxicities are the most frequent toxic manifestation of 5-fluorouracil (5-Fu) action in cancer patients. Hence, new approaches are required to deter chemotherapy-induced kidney toxicity. Nigella sativa (NS) is recognized as black cumin and has been found to be antiapoptotic, antioxidant, antimicrobial, anti-inflammatory and mitigates renal damage. Objectives: Thus, designed this work to evaluate the effect of NS in averting Nephrotoxicity induced by 5-FU treatment. Materials and Methods: Male albino Wistar rats were grouped and administered with saline, 5-FU group (150 mg/kg), 5-FU+NS (200 mg/kg) and 5-FU+NS (400 mg/kg), respectively. Rats were sacrificed on the 21st day, and biochemical, histological, serological and molecular estimations were done with kidney tissues and blood. 5-FU caused kidney injury as demonstrated by variations in kidney function markers (BUN, Cr, Kim-1), lipid peroxidation, histology and diminution of antioxidant guard machinery (GSH, GR, GPx and CAT). Additionally, 5-FU action changed p38 MAPK pathway proteins (p-p38, pJNK, pERK1/2, pNFkB, TNF-α) significantly. Conclusion: NS may serve as a potential candidate against renal injury by mitigating redox signaling, inflammation and p38 MAPK pathway. Therefore, NS could be used in adjuvant therapy for the prevention of Nephrotoxicity in cancer patients caused by 5-FU.
Keywords: 5-FU; p38MAPK pathway; Inflammation; Oxidative stress; ROS; Nigella sativa